Peace and Conflict Impact Assessment of the Niger Delta Development Commission’s Inter-Ventions in Odi, Bayelsa State, Nigeria (2015)
Development interventions are aimed at promoting positive change, but they can equally have negative impact, especially in conflict-prone contexts. Whereas existing studies on Odi and the Niger Delta at large mainly focused on the history, environ-ment, culture, conflict and security situations, the peace and conflict impact of Nige-rian government‘s socio-economic interventions in the area have not been fully ex-plored. This study, therefore, assessed the Niger Delta Development Commission‘s (NDDC) interventions, to determine their relationship with the Commission‘s man-date, strategies, and community needs; their interactions with the community; and their impact on the dynamics of peace and conflict in Odi, a community that has at-tracted many interventions after the 1999 massacre. The study adopted the grounded theory and case study research designs. Primary and secondary data were collected through key informant and in-depth interviews, official documents and non-participant observation. Fifty-four key informant interviews were conducted with seven members of the Traditional Ruling Council and the Community Development Committee, six religious leaders, five women leaders, five Youth Coun-cil executives, 24 project beneficiaries, 12 NDDC staff, and five NDDC consultants. Forty-seven in-depth interviews were also held with six school teachers, ten politi-cians, and two law enforcement agents in Odi, five international/non-governmental organisations staff, six activists, and eight academics and professionals. The Niger Delta Regional Development Master Plan, the NDDC Act, and website contents were consulted. Non-participant observations were carried out at NDDC project sites in Odi. The data gathered were content analysed. The NDDC integrated development strategy correlated with NDDC‘s mandate and people‘s needs. However, the Commission, in implementing its interventions, contra-vened some of its articulated guiding principles and policies like promoting good gov-ernance, transparency, participatory decision-making, and impact assessment. Also, inadequate community consultation caused dissonance in NDDC‘s and community‘s prioritisation of needs. Moreover, due to inadequate consideration for peace and con-flict sensitivity, the interventions produced series of positive and negative impact on peace and conflict dynamics in Odi. Construction of roads and educational facilities, rural electrification and training in modern agricultural practices impacted positively on the structural causes of conflict. They brought federal government‘s presence to Odi; provided income for male youths employed as labourers and for construction ma-terials‘ suppliers as well as capacity building in modern agricultural practices. How-ever, the community perceived the NDDC interventions as resources and competed for in a socio-political environment characterised by pervasive corruption and bad gov-ernance. This provided sufficient conditions for spirals of negative consequences that ultimately reduced the overall effectiveness of the interventions. The negative impact included entrenching corruption in intervention cycle, power disequilibrium between NDDC and Odi community, oppression and division, and gender inequality, commu-nal conflicts, and apathy. The Niger Delta Development Commission‘s interventions, intended for positive change, also had many negative consequences in Odi because the Commission failed to mainstream peace and conflict sensitivity in the interventions. The NDDC should therefore adhere strictly to its guiding principles and policies as well as international best practices in intervention programming in order to maximise the positive and minimise the negative impacts of its interventions.